Diversity of Phytoplankton in the Solok Pulau Lake, Tanjung Balam Village, Siak Hulu Sub-Regency, Kampar Regency, Riau Province - Hendri Andriawan; Windarti '; Efawani ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
A study on the diversity of phytoplankton in the Solok Pulau Lake was conducted fromOctober–December 2015. This research aims to understand the diversity and abundance ofplankton in that area. There were three stations with 3 sampling points in each station. Sampleswere taken 3 times, once a week and they were analyzed in the Aquatic Productivity Laboratoryoh the Fisheries and Marine Science Faculty, Riau University.Result shown that the phytoplankton obtained were consist of 22 species, they werebelonged to of 6 classes, Bacillariophyceae (4 species), Chlorophyceae (10 species),Cyanophyceae (3 species), Dinophyceae (1 species), Euglenophyceae (3 species) danXantophyceae (1 species). The average of phytoplankton abundance was around 553 – 17.778cells/l. The most common phytoplankton was Isthmia sp. (28.978 cells/L, Bacillariophyceae).Diversity index (H’) was 2.47 – 3. 54 and dominancy index (C) was 0.11 – 0.21. General waterquality parameters are as follow: temperature: 28 – 30 °C, pH: 6, brightness: 38 – 70.5 cm, DO:6.7 – 7.6 mg/L, CO2: 9.8 – 12.7 mg/L, Nitrate: 0.02 – 0.04 mg/L and phosphate: 0.09 – 0.018mg/L. Based on phytoplankton abundance, the Solok Pulau Lake can be categorized asoligotrophic lake.Keywords : Phytoplankton Diversity, Bacillariophyceae, Solok Pulau Lake